1972
DOI: 10.1111/j.1752-7325.1972.tb03979.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Oral Hygiene as a Function of Applied Principles of Behavioral Modification

Abstract: Dr. Stacey has planned and reported a novel investigation of technics for motivating improved oral hygiene in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Stacey and coworkers have demonstrated that both an increased dental knowledge and an effective application of this knowledge by patients are necessary in order to improve oral cleanliness. They concluded that the patient must be shown the proper brushing technique and taught the importance of dental health for achieving the desired level of dental hygiene . Moreover, since regular reinforcement was done, it could have resulted in the better uptake of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stacey and coworkers have demonstrated that both an increased dental knowledge and an effective application of this knowledge by patients are necessary in order to improve oral cleanliness. They concluded that the patient must be shown the proper brushing technique and taught the importance of dental health for achieving the desired level of dental hygiene . Moreover, since regular reinforcement was done, it could have resulted in the better uptake of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the patient must be shown the proper brushing technique and taught the importance of dental health for achieving the desired level of dental hygiene. 19 Moreover, since regular reinforcement was done, it could have resulted in the better uptake of knowledge. Several other investigations have confirmed that multiple reinforcements along with one-on-one oral hygiene instructional program lasting for at least 3 months can maintain improved oral hygiene in children for the duration of the program.…”
Section: Clinical Variable School a School B T-value Df P-value Schoomentioning
confidence: 99%
“…Only two studies concerned patients with mild disabilities, one of which found "modest" improvements (Stacey, Abbott & Jordan, 1972) with an information plus feedback procedure. The other study paradoxically found better results from the group that was not exposed to an information intervention (Boj & Davila, 1989).…”
Section: Information/education/instructionmentioning
confidence: 99%
“…Two studies were done on patients with special needs. One found “modest improvements” (Stacey, Abbott & Jordan, 1972). Another found “substantial decreases” in uncooperative behavior for four children with mild/severe disabilities as a function of the contingent presentation of stickers exchangeable for prizes (Allen and Stokes, 1987).…”
Section: Behavior Modification Techniques Applied To Resistance To De...mentioning
confidence: 99%
“…Moderately effective results were obtained regarding the improvement of their oral hygiene skills. [ 5 ] Sprod et al ., 1996 suggested that health promotion in schools conducted in a comprehensive and interesting way might benefit the oral health status of the children. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%